Thoughts and feelings of law students in their contact with the Workplace - del Mastro Puccio, Fernando (2022)
In Peru, law students must complete a preprofessional internship period. Despite the relevance of these experiences as their first encounter with the reality of the professional practice, there are no investigations that inquire into their impact on the student learning process. In this article, based on a theoretical framework around Hannah Arendt and the narrative analysis of students accounts, we seek to identify and understand how frozen thoughts operate in their experience as trainees.In our analysis, we identified the following frozen thoughts: (i) it is necessary to work in excess in order to learn, (ii) mistreatment is acceptable if everyone is subject to it and (iii) tasks must be carried out without thinking or questioning them. Even though these thoughts are transmitted to the students in grave situations of legal non-compliance, mistreatment, and the commission of professional ethic violations, they act as expected without saying or doing anything. What reigns in them is the fear of not being valued, and not a process of reflection where they can question what they’re being told. There are, however, cases where students do doubt that these thoughts are correct, but the inner conflict is left unresolved.The relevance of this work lies in showing part of what happens in a training environment that has a great impact on learning, but has been neglected. In particular, it shows ways in which emotional factors, such as the desire to be recognized and self-worth doubt, works as barriers in the processes of thought and action. Finally, at the level of pedagogical reflection, Socratic pedagogy is presented as an approach that can have good results at the level of ethical training of students who experience situations such as those analyzed.